Efficacy and safety with ticagrelor in patients with prior myocardial infarction in the approved European label: insights from PEGASUS-TIMI 54. Issue 4 (20th June 2019) - Dellborg, Mikael; Bonaca, Marc P; Storey, Robert F; Steg, P Gabriel; Im, Kyung A; Cohen, Marc; Bhatt, Deepak L; Oude Ophuis, Ton; Budaj, Andrezej; Hamm, Christian; Spinar, Jindrich; Kiss, Robert G; et al.
Abstract: Aims: In PEGASUS-TIMI 54, ticagrelor significantly reduced the risk of the composite of major adverse cardiovascular (CV) events by 15–16% in stable patients with a prior myocardial infarction (MI) 1–3 years earlier. We report the efficacy and safety in the subpopulation recommended for treatment in the European (EU) label, i.e. treatment with 60 mg b.i.d. initiated up to 2 years from the MI, or within 1 year after stopping previous adenosine diphosphate receptor inhibitor treatment. Methods and results: Of the 21 162 patients enrolled in PEGASUS-TIMI 54, 10 779 patients were included in the primary analysis for this study, randomized to ticagrelor 60 mg ( n  = 5388) or matching placebo ( n  = 5391). The cumulative proportions of patients with events at 36 months were calculated by the Kaplan–Meier (KM) method. The composite of CV death, MI, or stroke occurred less frequently in the ticagrelor group (7.9% KM rate vs. 9.6%), hazard ratio (HR) 0.80 [95% confidence interval (CI) 0.70–0.91; P  = 0.001]. Ticagrelor also reduced the risk of all-cause mortality, HR 0.80 (0.67–0.96; P  = 0.018). Thrombolysis in myocardial infarction major bleeding was more frequent in the ticagrelor group 2.5% vs. 1.1%; HR 2.36 (1.65–3.39; P  < 0.001). The corresponding HR for fatal or intracranial bleeding was 1.17 (0.68–2.01; P  = 0.58). Conclusion: In PEGASUS-TIMI 54, treatment with ticagrelor 60 mg as recommended in the EU label, was associated with a relative risk reduction of 20% in CV death, MI, or stroke. Thrombolysis in myocardial infarction major bleeding was increased, but fatal or intracranial bleeding was similar to placebo. There appears to be a favourable benefit-risk ratio for long-term ticagrelor 60 mg in this population. Clinical trial registration: http://www.clinicaltrials.gov NCT01225562